Factors influencing ICT adoption in cultural preservation among ethnic minorities in Malaysia - Choo, Yeong Khong; Gill, Sarjit S.; Talib, Ahmad Tarmizi (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2017)
This paper aims to discuss the current situation of the adoption of Information and Communication Technology (ICT) in cultural preservation among ethnic minorities in Malaysia. The emergence of the ICT in the present knowledge-based digital era has become a basic necessity of human beings in managing their daily lives. Despite increased research interest on ICT adoption, it has been surprisingly lack of empirical studies in addressing the potential role of ICT in cultural preservation among the ethnic minorities in Malaysia. This study is important because many ethnic minorities in Malaysia are experiencing digital divide and facing the threat of losing their cultural identity through various means such as the being assimilated into the mainstream society. As the sophisticated technologies nowadays have penetrated almost every aspect of human lives, is it appropriate to still holding a pessimistic perception which label ICT as the agent that eroded the culture but ignoring the potential of ICT in cultural preservation? To what extent the ethnic minorities adopted ICT to preserve their culture? What are the factors influencing ICT adoption in cultural preservation among the ethnic minorities? Hence, this paper aims to debate the concerns as stated above.